Detection of secondary upper gastrointestinal tract cancer during follow‐up esophagogastroduodenoscopy after gastrectomy for gastric cancer - Kosuke Nakane; Keiichi Fujiya; Masanori Terashima; Takanori Kawabata; Yosuke Matsumoto; Satoshi Kamiya; Makoto Hikage; Yutaka Tanizawa; Hiroyuki Ono; Etsuro Bando (Annals of Gastroenterological Surgery, 2022)
Abstract Aim Esophagogastroduodenoscopy (EGD) may contribute to early detection of secondary cancer in the upper gastrointestinal tract although the clinical relevance of follow‐up after gastrectomy remains unclear. This study aimed to elucidate the effectiveness of follow‐up EGD by investigating the incidence of secondary cancer in any part of the upper gastrointestinal tract. Methods Data from 1438 patients who underwent curative partial gastrectomy for primary gastric cancer between 2008 and 2014 and follow‐up EGD at least once during a 5‐year follow‐up period were retrospectively reviewed. Incidence rates of remnant gastric cancer, laryngeal cancer, and esophageal cancer detected after follow‐up EGD were determined, and risk factors for secondary cancers were examined. The characteristics of clinicopathological diagnoses of secondary cancers were reviewed and compared according to the frequency of follow‐up EGD. Results The average annual frequency of EGD was 0.7, while the 5‐year cumulative incidence rates of remnant gastric cancer and secondary laryngeal and esophageal cancers were 2.9% and 1.3%, respectively. Risk factors for remnant gastric cancer included heavy smoking, proximal gastrectomy, and tumor size ≥ 30 mm. All secondary cancers were resectable upon diagnosis, with endoscopically resectable cancer accounting for 81.0% of cases. Our results found a significantly higher proportion of endoscopically resectable cancers during regular follow‐up than during infrequent follow‐up. Conclusions Follow‐up EGD can be a useful modality for detecting secondary upper gastrointestinal tract cancer, likely leading to curative treatment for secondary cancer. Focusing on patients presenting with risk factors may increase the value of follow‐up EGD after gastrectomy.